Beach-Based Educational Games to Enhance Children’s Creativity in Banten and Jakarta - Sri Nuraini; Masnur Ali; Taufik Rihatno; Qory Jumrotul Aqobah (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aims to develop and evaluate a beach-based educational game model as an intervention to enhance the creativity of elementary school-aged children in the coastal areas of Banten and the city of Jakarta. The study employs a quasi-experimental approach with a non-randomized control group design, involving two groups: an intervention group that participated in the beach educational game program and a control group that continued with conventional learning methods. Creativity was measured using a valid instrument that assessed several dimensions of creativity: fluency (idea generation), originality, flexibility (flexibility of thinking), elaboration (depth of detail), and risk-taking (willingness to try new things). Data were analyzed using analysis of variance (ANOVA) and analysis of covariance (ANCOVA) to account for demographic variables and coastal environmental conditions. The results indicate that the beach-based educational game model significantly enhances children’s creativity dimensions, with the greatest improvements observed in flexibility and originality. A stronger effect was evident in the coastal areas of Banten compared to Jakarta, likely due to direct access to the beach enviro.